Intracellular ROS Scavenging and Anti-Inflammatory Activities of Oroxylum indicum Kurz (L.) Extract in LPS plus IFN-γ-Activated RAW264.7 Macrophages. (27th May 2020) - Dunkhunthod, Benjawan; Talabnin, Chutima; Murphy, Mark; Thumanu, Kanjana; Sittisart, Patcharawan; Hengpratom, Tanaporn; Eumkeb, Griangsak
Abstract : Oroxylum indicum (L.) Kurz has been used as plant-based food and herbal medicine in many Asian countries. The aim of the present study was to examine the antioxidant and anti-inflammatory activities of O. indicum extract ( O. indicum ) in RAW264.7 cells activated by LPS plus IFN- γ . The phytochemical compounds in O. indicum were identified by GC-MS and LC-MS/MS. Five flavonoids (luteolin, apigenin, baicalein, oroxylin A, and quercetin) and 27 volatile compounds were found in O. indicum . O. indicum presented antioxidant activities, including reducing ability by FRAP assay and free radical scavenging activity by DPPH assay. Moreover, O. indicum also suppressed LPS plus IFN- γ -activated reactive oxygen species generation in RAW264.7 macrophages. It possessed the potent anti-inflammatory action through suppressing nitric oxide (NO) and IL-6 secretion, possibly due to its ability to scavenge intracellular ROS. The synchrotron radiation-based Fourier transform infrared (SR-FTIR) spectroscopy results showed the alteration of signal intensity and integrated areas relating to lipid and protein of the activated RAW264.7 macrophages compared to unactivated cells. This is the first report of an application of the SR-FTIR technique to evaluate biomolecular changes in activated RAW264.7 cells. Our results indicate that O. indicum may be used as a potential source of nutraceutical for the development of health food supplement or a novel anti-inflammatory herbal medicine.